SURVEILLANCE OF HOUSEHOLD CLEAN AND HEALTHY BEHAVIOR (PHBS) IN LAM GURON VILLAGE, PEUKAN BADA DISTRICT, ACEH BESAR - Siti Rahmah; Hidayattullah, mhd; Juliana; Malena; Yara Yulia; Khairunnisa; Balqis , Putri (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
The implementation of Clean and Healthy Behavior is a culture of life for individuals, families, and communities that is healthy-oriented and aims to improve, maintain, and protect their physical, mental, and social health. This research is a descriptive-analytic study and conducted direct interviews with respondents using a structured questionnaire. Of the ten indicators, respondents who did not apply PHBS based on the most indicators were in the larva eradication indicator. Respondents who did not eradicate larvae were 20 (35%) out of a total of 57 (100%) respondents. It is hoped that the community can do 3M Plus so that they don't just know but also apply it in their daily life so that their environment is free from larvae and does not pose a risk of dengue hemorrhagic fever.